Comparison of Interferon-Related Gene Expression Profiles in the Cells Infected with Human and Avian Type Influenza A Viruses - TURAN, KADİR (My University, 2020)
Introduction: Influenza A viruses can cause flu outbreaks in humans with high rates ofmorbidity and mortality worldwide, and is regarded as a major global health threat. The virushost specificity and pathogenicity not only depend on viral factors, but also host intracellulardefense mechanisms play an important role. Therefore, the elucidation of complex interactionsbetween the host and viruses is the most important point of the studies.Material and Methods: The transcript of interferon related 84 genes (RT² Profiler PCR Array)have been quantified in the cDNAs prepared from HEK-293 cells virus infected with humantypeinfluenza A/WSN/33/H1N1 (WSN) and avian type InfluenzaA/duck/Pennsylvania/10,218/84/H5N2 (DkPen) viruses. Quantitation of interferon-relatedgenes transcripts was carried out with quantitative real-time polymerase chain reaction (qRTPCR).The assay was repeated at least three times for each group. The statistical significanceof differences between experimental groups was evaluated using analysis of variance (one-wayANOVA with Newman-Keuls post test) in the SPSS (p ≤ 0.05).Results: qRT-PCR analysis showed that, 35 genes were found to be upregulated and 20 genesfound to be downregulated in the cells infected with influenza A/WSN virus compared touninfected cells. It was found that the most increased transcripts in the cells infected with WSNviruses were encoded by the genes; CCL5 (160 fold), HLA-G (275 fold), (IFIT2) (81 fold),IFNB1 (185 fold), (IFNW1 (76 fold) and OAS1 (89 fold). The most decreased transcript in thecells infected with this virus was SOCS1 gene transcript (697 fold). On the other hand, 18 geneswere found to be upregulated and 33 genes found to be downregulated in the cells infected withinfluenza A/DkPen. The highest increase values were detected in the transcripts of CCL5 (33-fold), HLA-G (980-fold), IFNB1 (92-fold) and OAS1 (28-fold) genes. The genes whose themost decreased transcript levels were OAS2 (627-fold) and SOCS1 (18-fold) genes.Conclusion: It has been revealed that some interferon response genes give similar expressionprofiles in HEK293 cells infected with both human and avian influenza A viruses. In contrast,more interferon-related genes were down-regulated in DkPen infected cells comparing to WSNviruses (DkPen infected / 33 genes; WSN infected / 20 genes), while fewer genes were upregulated(DkPen infected / 18 genes; WSN infected / 35 genes). It was concluded that theinterferon related proteins are important in the replication efficiency of different types ofinfluenza viruses in infected cells.AcknowledgmentsThis work was supported by a grant from the Marmara University Research Foundation (grantno: SAG-C-DRP-250919-0291).
Keywords: Yaşam Bilimleri; Sağlık Bilimleri; Temel Bilimler; Life Sciences; Health Sciences; Natural Sciences; Klinik Tıp (MED); Temel Bilimler (SCI); Yaşam Bilimleri (LIFE); Doğa Bilimleri Genel; ÇOK DİSİPLİNLİ BİLİMLER; Clinical Medicine (MED); Natural Sciences (SCI); Life Sciences (LIFE); NATURAL SCIENCES, GENERAL; MULTIDISCIPLINARY SCIENCES; Multidisipliner; Multidisciplinary